2010
DOI: 10.1136/vr.b4879
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor gene expression in the accessory sex glands of veal calves

Abstract: This study investigated progesterone receptor (PR) cDNA expression in the testes, prostate and bulbourethral glands of prepubertal calves treated experimentally with high and low doses of 17beta-oestradiol and with testosterone. Tissue samples were examined histologically and immunohistochemically for PR. Western blot analysis and quantitative PCR against PR was performed on cDNA and protein extracted from the same tissues. Bulbourethral glands from animals treated with low and high dosages of 17beta-oestradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 38 publications
(40 reference statements)
4
30
0
Order By: Relevance
“…The present study examined a novel strategy based on PR gene expression in adult male accessory sex glands in response to 17-oestradiol that was administered either alone or in combination with other molecules to reveal growth promoter abuse. In this experiment, in addition to the typical epithelial hyperplastic and metaplastic changes that were observed in the prostate, urethra and bulbourethral glands (Biolatti et al 2003;Groot et al 2007;De Maria et al 2010), 17-oestradiol induced significant PR transcriptional up-regulation in the prostate (25.07-fold) and bulbourethral glands (23.42-fold). These data were confirmed by a protein expression analysis using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The present study examined a novel strategy based on PR gene expression in adult male accessory sex glands in response to 17-oestradiol that was administered either alone or in combination with other molecules to reveal growth promoter abuse. In this experiment, in addition to the typical epithelial hyperplastic and metaplastic changes that were observed in the prostate, urethra and bulbourethral glands (Biolatti et al 2003;Groot et al 2007;De Maria et al 2010), 17-oestradiol induced significant PR transcriptional up-regulation in the prostate (25.07-fold) and bulbourethral glands (23.42-fold). These data were confirmed by a protein expression analysis using immunohistochemistry.…”
Section: Discussionmentioning
confidence: 67%
“…All groups were housed in separate boxes and fed a concentrated diet consisting of corn silage, corn, hay, and a commercial protein supplement; water was supplied ad libitum. Hormone dosages were chosen according to the literature (Vanderwal et al 1975;Meyer 2001;Cannizzo et al 2008;De Maria et al 2010).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, the transcriptomic approach could facilitate the identification of biomarkers suitable for the detection of illegally treated animals. Recent studies have shown that progesterone receptor (PR) gene expression levels were increased in the bulbo-urethral and prostate glands of 17β-estradiol-treated calves and beef cattle [53], [57]. For potential use in food safety monitoring, a quantitative PCR (qPCR) method has been developed for the detection of up-regulated PR gene expression in the bulbo-urethral glands of beef cattle and veal calves illegally administered 17β-estradiol [58].…”
Section: Introductionmentioning
confidence: 99%
“…The hormone dosages were selected according to previous studies. 2,21,22 The Tissue Sampling and Processing. Samples of bulbo-urethral glands, prostate and testis tissues were obtained from each animal at slaughter.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%